China past forward - forever Beijing - Chang, Liu.; Randle, Jim.; Wolf, Erika; Gibbons, James; Discovery Channel (Firm).; Discovery Communications, Inc.; China Action Limited; Discovery Networks Asia. (Bethesda, Mid. Discovery Communications, 2003)
Not too far from the Forbidden City, Beijing's secret treasures are slowly vanishing. This program captures the dilemmas, contemporary and otherwise, faced by a people undergoing rapid change in their new century.
Executive producer: Erika Wolf ; Executive in charge of production: James Gibbons.
Narrator: Jim Randle.
VCD.
Keywords: Historic sites -- China -- Beijing; Architecture -- China -- Beijing -- History; Alleys -- China -- Beijing; Beijing (China) -- Social life and customs